2017
DOI: 10.1097/iae.0000000000001443
|View full text |Cite
|
Sign up to set email alerts
|

Acute Central Serous Chorioretinopathy

Abstract: The investigation of clinical and multimodal imaging factors influencing the duration of first, acute, and treatment-naive CSCR episodes by survival analysis showed that higher subfoveal choroidal thickness, higher pigment epithelial detachment or bump at leakage sites, and older age were independent predictors of longer episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 45 publications
5
59
0
9
Order By: Relevance
“…To the best of our knowledge, this is the first study on the association between CNV detected by OCTA and choroidal thickness in chronic CSCR. CT was increased in the evaluated group, both in the affected and fellow eyes, which is consistent with other reports [ 9 14 , 34 ]. Our study did not reveal any statistically significant correlations between CT and the occurrence of CNV and type of PED.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study on the association between CNV detected by OCTA and choroidal thickness in chronic CSCR. CT was increased in the evaluated group, both in the affected and fellow eyes, which is consistent with other reports [ 9 14 , 34 ]. Our study did not reveal any statistically significant correlations between CT and the occurrence of CNV and type of PED.…”
Section: Discussionsupporting
confidence: 92%
“…The positive correlation between CT and risk of CSCR recurrences was also described [ 14 ]. Daruich et al revealed increased choroidal thickness as a factor which influences episode duration in acute CSCR [ 34 ]. Based on previous studies, we might conclude that thicker choroid is a predictor of the worse course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Durch die neurosensorische Abhebung kann es zudem zu einer Hypermetropisierung kommen. Der Spontanverlauf der akuten CCS ist günstig und die subretinale Flüssigkeit wird in 68 % der Fälle innerhalb von 4 Monaten und in 84 % der Fälle innerhalb von 6 Monaten nach Erstdiagnose resorbiert [19]. Trotz der Remission der subretinalen Flüssigkeit können die Patienten langfristig unter Metamorphop-sie, reduzierter Kontrastsensitivität und Farbsehalterationen leiden [88].…”
Section: Einteilung Und Klinikunclassified
“…Spontaneous course 4 The literature puts spontaneous remission of SRF at 68% within 4 months and 84% within 6 months of initial diagnosis [19]. Recurrent accumulation of SRF in the further course is seen in approximately 50% of cases.…”
Section: Grade Of Recommendation: ⇑⇑mentioning
confidence: 99%
“…Neurosensory detachment can also lead to hypermetropization. The spontaneous course of CSC is favorable and SRF absorbs within 4 months of initial diagnosis in 68% of cases and within 6 months in 84% [19]. Despite remission of SRF, patients may experience long-term metamorphopsia, reduced contrast sensitivity, and altered color vision [88].…”
Section: Classification and Symptomsmentioning
confidence: 99%